2021
DOI: 10.1111/cdoe.12620
|View full text |Cite
|
Sign up to set email alerts
|

The association of maternal folic acid supplementation and prenatal folate and vitamin B12 concentrations with child dental development

Abstract: Objective Low folic acid, folate and vitamin B12 might affect tooth formation and mineralization. The conversion of folic acid into folate is catalysed by the methylenetetrahydrofolate (MTHFR) enzyme which is encoded by the MTHFR gene. Among 3728 mothers and their 10‐year‐old children from the Generation R Study, we investigated associations of maternal folic acid supplementation and prenatal folate and vitamin B12 concentrations with child dental development. Secondly, we checked the modifying effect of MTHFR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Since teeth formation starts in utero, one must question whether the patient's underlying disorder impacting folate or methylation could be explained prenatally. Moreover maternal folate consumption has an important role in tooth development as observed by Dhamo [ 14 ], but that role is still not fully understood. Via their prospective cohort study, they were able to observe that folate supplementation pre-conceptionally or post-conceptionally can affect the dental age (speed of development of dentition) by 1–2 months in children.…”
Section: Discussionmentioning
confidence: 99%
“…Since teeth formation starts in utero, one must question whether the patient's underlying disorder impacting folate or methylation could be explained prenatally. Moreover maternal folate consumption has an important role in tooth development as observed by Dhamo [ 14 ], but that role is still not fully understood. Via their prospective cohort study, they were able to observe that folate supplementation pre-conceptionally or post-conceptionally can affect the dental age (speed of development of dentition) by 1–2 months in children.…”
Section: Discussionmentioning
confidence: 99%
“…In a study about maternal and neonatal 25(OH)D concentrations and dental development in childhood, lower vitamin D levels during mid-pregnancy or at birth were associated with higher dental age of children, and higher developmental stages of the mandibular teeth [ 71 ]. Maternal folic acid supplementation delays dental development of children by 1–2 months of dental age, whereas maternal folate and vitamin B 12 concentrations in early pregnancy do not affect the timing of a child’s dental development [ 72 ].…”
Section: Research Outcomesmentioning
confidence: 99%
“…Deficiency of folic acid is usually said to have its association with neural tube defects and a reduction in cleft lip/cleft palate has been observed when pregnant women take folic acid supplement ( Burgess et al , 2018 ; Van rooij et al , 2004 ;). Folic acid deficiency also impairs the sulcular barrier function ( Burt, 1982 ; Dhamo et al , 2021 ), and few studies have suggested that supplementation with folate might help in reducing the gingival fluid flow as well as the bleeding index. Vitamin B12 is known to contribute towards mucosal wound healing and facilitating bone health, both of which are necessary for recovery in cases of periodontitis.…”
Section: Introductionmentioning
confidence: 99%